2013
DOI: 10.1149/2.071308jes
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Capacity in Mn-Based/Graphite Commercial Lithium-Ion Batteries

Abstract: Commercially available lithium-ion batteries (LiMn 2 O 4 /LiNi 0.8 Co 0.15 Al 0.05 O 2 mixed cathode and graphite anode) are disassembled to determine the reversible capacity of each electrode, the state of charge (SOC) in the operation range, and the lithium content in the graphite anode by inductively coupled plasma optical emission spectroscopy (ICP-OES) after a cycle or storage operation. The origin of the decrease in capacity of the battery is attributed to (i) the decrease in capacity of the cathode acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…Therefore the result suggested that the decomposition of electrolyte and positive electrode material was drastically accelerated at high-operating temperature at 45 • C. On the contrary, the unclear temperature dependences of Li, F, and Mn suggested SEI formation and Mn deposition occurred rather independently of the operating temperature. This might be related with the preceding results that the contribution of capacity loss in the positive electrode was dominant factor for the capacity degradation at the operating temperature of 45 • C, and that SEI formation was dominant for the degradation for the operation at 25 • C. 7 Depth profile of the whole graphite electrode layer.- Figure 6 presents qualitative and quantitative GD-OES depth profiles of the whole graphite electrode layer for C45-600. Data were taken using 1.00 % H 2 v/v added Ar gas (Ar-H 2 ).…”
Section: Sei Growth and Mn Deposition On Graphite Electrode Surface-supporting
confidence: 68%
“…Therefore the result suggested that the decomposition of electrolyte and positive electrode material was drastically accelerated at high-operating temperature at 45 • C. On the contrary, the unclear temperature dependences of Li, F, and Mn suggested SEI formation and Mn deposition occurred rather independently of the operating temperature. This might be related with the preceding results that the contribution of capacity loss in the positive electrode was dominant factor for the capacity degradation at the operating temperature of 45 • C, and that SEI formation was dominant for the degradation for the operation at 25 • C. 7 Depth profile of the whole graphite electrode layer.- Figure 6 presents qualitative and quantitative GD-OES depth profiles of the whole graphite electrode layer for C45-600. Data were taken using 1.00 % H 2 v/v added Ar gas (Ar-H 2 ).…”
Section: Sei Growth and Mn Deposition On Graphite Electrode Surface-supporting
confidence: 68%
“…6 The loaded weight of the cathode without the aluminum current collector was 21 mgcm −2 . The counter anode was graphite, and the loaded weight of the anode without the copper current collector was 8 mgcm −2 .…”
Section: Methodsmentioning
confidence: 99%
“…One way to overcome this problem is not to consider the average surface capacity (in mAh/cm 2 ) of the samples, but to consider the average weight of the samples harvested from "fresh" electrodes before building coin-cells to calculate and compare the mass capacity (in mAh/g). Kobayashi 12 The residual capacity of cathodes harvested from cells after cycling or calendaric aging (converted in the cathode SOC in the discharge state) increased if compared with the value obtained for the fresh cell. 12 The authors demonstrated that there is a relationship between the capacity retention of the studied cell and the SOC of the cathode in the discharge state (identically with the open-circuitvoltage of the half coin-cell that deduces the state of lithiation of the electrode).…”
mentioning
confidence: 97%
“…Kobayashi 12 The residual capacity of cathodes harvested from cells after cycling or calendaric aging (converted in the cathode SOC in the discharge state) increased if compared with the value obtained for the fresh cell. 12 The authors demonstrated that there is a relationship between the capacity retention of the studied cell and the SOC of the cathode in the discharge state (identically with the open-circuitvoltage of the half coin-cell that deduces the state of lithiation of the electrode). 12 That suggests that Li ions are not only irreversibly stored on the anode side in the initial SEI formation cycle but also continuously accumulated during cycling or calendaric aging.…”
mentioning
confidence: 97%
See 1 more Smart Citation